2016
DOI: 10.1002/cm.21283
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray fiber diffraction analysis shows dynamic changes in axial tubulin repeats in native microtubules depending on paclitaxel content, temperature and GTP‐hydrolysis

Abstract: Microtubules are key components of the cytoskeleton in eukaryotic cells. The dynamics between assembled microtubules and free tubulin dimers in the cytoplasm is closely related to the active shape changes of microtubule networks. One of the most fundamental questions is the association of microtubule dynamics with the molecular conformation of tubulin within microtubules. To address this issue, we applied a new technique for the rapid shear-flow alignment of biological filaments, enabling us to acquire the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 54 publications
4
34
0
Order By: Relevance
“…The shorter pitch of GDP microtubules without KIF5C is in agreement with our previous results with GDP microtubules with a substoichiometric concentration of Taxol measured using the same method (Kamimura et al, 2016). The longer pitch with KIF5C is closer to the pitch of the GMPCPP microtubules measured at the same temperature (37°C).…”
Section: Resultssupporting
confidence: 92%
“…The shorter pitch of GDP microtubules without KIF5C is in agreement with our previous results with GDP microtubules with a substoichiometric concentration of Taxol measured using the same method (Kamimura et al, 2016). The longer pitch with KIF5C is closer to the pitch of the GMPCPP microtubules measured at the same temperature (37°C).…”
Section: Resultssupporting
confidence: 92%
“…Axial repeats r (Å) for each tubulin dimer were calculated to evaluate the compaction of the protein in the MT models along the simulation run, and were computed as the distance between the centers of mass of each subunit in the α 1 β 1 and α 2 β 2 dimers (Figure ). Average axial repeats for tubulin dimers in all systems under study lie in the range between 40.5 and 41.4 Å, which are in close agreement with previous resports . Despite no significant differences were observed among average axial repeats, distribution data revealed that PLA association impairs the axial repeat distribution between α 1 β 1 and α 2 β 2 dimers, unlike LAU and TX, which exhibit similar distribution patterns in both dimers.…”
Section: Resultssupporting
confidence: 89%
“…Average axial repeats for tubulin dimers in all systems under study lie in the range between 40.5 and 41.4 Å, which are in close agreement with previous resports. 33 ORCID Verónica A. Jiménez https://orcid.org/0000-0002-6783-5657…”
Section: Lateral Interdimeric Conformationmentioning
confidence: 99%
“…Final concentrations of protein, nucleotide and compounds were 50 µM tubulin, 1 mM GTP and 100 µM of compound. Samples were centrifuged for 10 s at 2000 g to eliminate air bubbles and transferred to a share-flow device (29,60).…”
Section: X-ray Fiber Diffractionmentioning
confidence: 99%